Echocardiographic Calcium Score of Aortic Valve Correlates with Coronary Artery Calcium Score in Heterozygous Familial Hypercholesterolemia - Angelo Baldassare Cefalù; Emilio Nardi; Antonina Giammanco; Carola Maria Gagliardo; Carlo Maria Barbagallo; Ludovico La Grutta; Patrizia Toia; Federica Brucato; Chiara Scrimali; Teresa Maria Grazia Fasciana; Rossella Spina; Marina Lanza; et al. (Life)
Background: Patients with heterozygous familial hypercholesterolemia (HeFH) are at a high risk of atherosclerotic cardiovascular disease. The coronary artery calcification (CAC) score by the Ct-scan Agatston calcium score (ACS) > 100 classifies FH at a higher risk. The echocardiographic calcium score (ECS) evaluates aortic valve calcifications and is considered a good predictor of the atherosclerotic burden and cardiovascular outcome. Objective: To test the ECS as a predictor of ACS > 100 in a HeFH cohort. Methods: A coronary calcium CT scan with the calculation of ACS and an at rest-transthoracic echocardiogram with ECS evaluation were performed in 81 HeFH patients. Patients were divided into two groups according to the ACS: high-risk ACS patients (High-ACS) with Agatston value > 100 and low risk ACS patients (Low-ACS) with Agatston value ≤ 100. Patients were stratified according to ECS = 0 or ECS > 0. Results: High-ACS patients were older than Low-ACS patients; BMI, waist circumference, and blood systolic pressure were significantly higher (p < 0.001) in High-ACS patients. The ECS predicted an ACS > 100 with sensitivity = 0.84, specificity = 0.89, accuracy = 0.86, and precision = 0.76. Conclusions: The ECS could be a good surrogate of a coronary calcium CT scan for ACS evaluation in the specific subset of HeFH patients.